2016
DOI: 10.1097/cej.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Statins in the chemoprevention of colorectal cancer in established animal models of sporadic and colitis-associated cancer

Abstract: Despite the availability of effective surveillance for colorectal cancer with colonoscopy, chemoprevention might be an acceptable alternative. Statins are potent inhibitors of cholesterol biosynthesis. In clinical trials, statins have been found to be beneficial in the primary and secondary prevention of coronary heart disease. However, the overall benefits observed with statins appear to be greater than what might be expected from changes in lipid levels alone, suggesting effects beyond cholesterol lowering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Cholesterol medication use was significantly associated with reduced mRNA expression of PTGES1, and PTGES1 is the synthase that associates with PTGS2 (Table 1). This significant reduction in PTGES1 is consistent with data suggesting use of statins as a potential pharmacological approach for colon cancer prevention (30). Previous research also has indicated that combining NSAID use with cholesterol medications may be useful for CRC prevention and treatment (31).…”
Section: Discussionsupporting
confidence: 89%
“…Cholesterol medication use was significantly associated with reduced mRNA expression of PTGES1, and PTGES1 is the synthase that associates with PTGS2 (Table 1). This significant reduction in PTGES1 is consistent with data suggesting use of statins as a potential pharmacological approach for colon cancer prevention (30). Previous research also has indicated that combining NSAID use with cholesterol medications may be useful for CRC prevention and treatment (31).…”
Section: Discussionsupporting
confidence: 89%
“…In rat intestinal epithelium, this inhibition of isoprenylation by lovastatin was associated with induction of apoptosis which could be reversed by administration of GGPP. Induction of apoptosis has been described in several different mice models with various statins, suggesting a class effect 24 . In addition, statins may reduce formation of aberrant crypt foci and polyps, and reduce tumor metastasis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research suggests that statins may prevent various types of cancers, including colon [182184] and breast [185187] as well as ovarian, pancreatic, lung, and lymphomas, reviewed in [188]. Statins inhibit cancer cell proliferation by arresting the cell cycle at the G 1 -S phase and inducing apoptosis [189, 190].…”
Section: The Yin – Yang Of No and H2s In Carcinogenesismentioning
confidence: 99%